Analisis Kualitas Air Kali Surabaya terhadap Kandungan Logam Berat sebagai Air Baku PDAM Surabaya - Muh. Fredrik; Nieke Karnaningrum (Jurnal Serambi Engineering, 2024)
Domestic and industrial waste has been identified as containing many heavy metals as indicators in water bodies. The research aims to analyze the heavy metal quality of Surabaya river water and predict its quality as sustainable raw water. This research was located in the Surabaya River in the Karangpilang IPAM intake segment. The research method uses a forecasting approach based on primary data using a purposive sampling method and laboratory tests. The results showed that the heavy metal concentrations ofCr = <0.0117, Cu = <0.0090 and Pb = 0.001-0.010 did not exceed the quality standards based on class I classification of PP No. 22 of 2021 concerning Implementation of Environmental Protection and Management. The concentrations of heavy metals Cr and Cu are still lower than the detection limit of the test equipment, so forecasting is only carried out on the heavy metal Pb. The simulation results for the next 10 years still get results that meet the quality standards, but when compared with the actual ones with MAPE validation, there are several values that exceed the standards with very badforecasting levels.